The Chair of the U.S. Federal Reserve and the Macroeconomic Causality Regimes - Yunus Aksoy; Rubens Morita; Zacharias Psaradakis (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate regime-dependent Granger causality between real output, inflation and monetary indicators and map with U.S. Fed Chairperson's tenure since 1965. While all monetary indicators have causal predictive content in certain time periods, we report that the Federal Funds rate (FFR) and Domestic Money (DM) are substitutes in their role as lead or feedback variables to explain variations in real output and inflation. We provide a comprehensive account of evolution of causal relationships associated with all US Fed Chairpersons we consider.
Keywords: C32; C54; C61; E52; E58; 330; causality regimes; domestic money; Federal Reserve Chairperson; Markov switching; policy instrument; vector autoregression